Pengembangan Media Pembelajaran Game Interaktif Berbasis Platform Bamboozle Materi Cahaya, Bunyi dan Sifatnya Kelas V di SD Negeri 05 Indralaya - Mutmainnah; Siti Dewi Maharani; Esti Susiloningsih (EduInovasi: Journal of Basic Educational Studies, 2025)
This study aims to develop an interactive learning game based on the Bamboozle Platform for the topic of Light, Sound, and Their Properties for fifth-grade students at SD Negeri 5 Indralaya. The development process follows the ADDIE model, consisting of five stages: Analyze, Design, Development, Implementation, and Evaluation. Needs analysis revealed that learning media in schools are still dominated by conventional methods, necessitating digital innovations that are more engaging and interactive. During the development phase, the media was validated by media experts, material experts, and classroom practitioners. The validation results indicated that the developed learning media was categorized as "Highly Valid" with an average score of 95% and deemed "Highly Practical" by the classroom teacher with a score of 100%. After revisions based on expert suggestions, the media underwent individual and small-group trials. Student response questionnaires showed that the media was rated as "Highly Engaging" with an average score of 96.24%. The findings of this study suggest that interactive games based on the Bamboozle Platform effectively enhance student engagement and create a more enjoyable learning experience. Therefore, this media is recommended as an alternative for teaching science in elementary schools.